Advances In Research Of Spreading Through Air Spaces And The Effects On The Prognosis Of Lung Cancer - Cao D; Sha J; Cui R; Han S (Cancer Management and Research, 2019)
Dandan Cao,1,2 Jun Sha,1,2 Rui Cui,1,2 Shuhua Han1 1Department of Pulmonary Medicine, Zhongda Hospital, School of Medicine, South-East University, Nanjing, Jiangsu, People’s Republic of China; 2Medicine Department of Southeast University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Shuhua HanDepartment of Pulmonary Medicine, Zhongda Hospital, Ding Jia Qiao No. 87, Nanjing, Jiangsu 210009, People’s Republic of ChinaEmail hanshuhua0922@126.comAbstract: The concept of spread through air spaces (STAS) has been described as a new form of invasion in the lung in the 2015 WHO classiﬁcation of Lung Tumors, namely invasion through alveolar spaces. STAS is a prognostic factor independent of growth pattern and tumor stage, and it is also an independent risk factor for unfavorable prognosis of stage I lung adenocarcinoma (ADC) and stage I lung squamous cell carcinoma (SCC). The pathological characteristics are different between ADC and SCC. STAS is not reported as routine, so setting a unified pathological reading standard, and hunting for STAS as a regular reading process is urgently advocated. We write this review to investigate the research progress of STAS and its effects on the prognosis of lung cancer.Keywords: lung cancer, STAS, pathological characteristics, prognosis